Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Hawassa University - International Livestock Research Institute; Hawassa University (2021)
Memorandum of understanding (MOU) between the International Livestock Research Institute (ILRI) and Hawassa University. MOU signed on December 23, 2021, by Jimmy Smith, Director-General of ILRI and Tarekegn Yoseph, College Dean at Hawassa University.